STUDENTS IN OBESITY Prevalence of COURSE OF THE NATIONAL PROGRAM FOR INTEGRATION OF BASIC EDUCATION, THE MODE OF ADULT AND YOUTH EDUCATION - PROEJA IN FEDERAL PUBLIC SCHOOL, THE MARSHAL DEODORO CITY - AL. (Fiep Bulletin - online, 2016)
Obesity, defined according to the World Health Organization in 1998 as "disease in which excess body fat has accumulated to such an extent that health may be affected." It is a universal disease of growing prevalence epidemic, one of the major public health problems of modern society. (LOPES, 2006). This study aims to determine the obesity prevalence level students of the national program courses integration of basic education, youth education mode and adults - PROEJA in federal public school in the municipality of Marechal Deodoro, Alagoas. It is a cross-sectional study of analytical and quantitative approach. Risks which is to conduct this research is the possibility of all (the) students give up to participate in this work and possible strikes at the Federal Institute of Alagoas, Marechal Deodoro Campus - Al.
Keywords: prevalence; obesity; Proeja.